Ways of Formation of Information Culture of Schoolchildren of the Oldest Classes in the Work With Electronic Educational Sources (Journal of Educational Sciences, 2018)
In the article the meaning of such notions as «information», «informatization», «information and computer literacy» and computer culture are disclosed. Currently, all knowledge is the professional skillsof the individual associated with the information culture. Personal information culture is the ability to perform professional, educational self-education and other activities, as well as an important factor inensuring social protection of the individual. Nevertheless, as show studies by scientists and our practice, it is impossible to achieve such results in traditional education. For this it is necessary to improve the level of pedagogical technology in education, as well as the issues of the development of the information culture and its significance and consideration of the individual feature of the student.Key words: informatization of education, information technologies, information culture